Single-Center Experience of Cerecyte Coils in the Treatment of Intracranial Aneurysms: Initial Experience and Early Follow-Up Results - Butteriss, D.; Gholkar, A.; Mitra, D.; Birchall, D.; Jayakrishnan, V. (American Journal of Neuroradiology, 2008)
BACKGROUND AND PURPOSE: Endovascular treatment of intracranial aneurysms using platinum coils is effective, but uncommonly aneurysms recur. New-generation coils, such as Cerecyte, aim to address this problem. This study examines the safety and efficacy of these coils in the treatment of a cohort of ruptured and unruptured aneurysmsMATERIALS AND METHODS: Sixty-seven patients with 68 aneurysms were included in the study. Of these, 51 were treated exclusively with the new polyglycolic acid (PGA)-containing coils, and 17 were treated with a combination of new PGA-containing and other coils. Initial and follow-up angiograms were graded according to the 3-point scale of occlusion. Follow-up angiography was available in 46 cases at 6 months. Based on occlusion grading at initial and follow-up angiography, aneurysms were classified into stable, improved, and worsened (recanalized) groups.RESULTS: Of the exclusive new-coil cohort, 36 cases (70.6%) were initially completely occluded (grade 1), 12 (23.5%) showed filling at the neck (grade 2), and 3 (5.9%) showed contrast within the neck and sac (grade 3). Analysis of the follow-up angiograms showed 24 (70.6%) had stable occlusion, 3 (8.8%) had improved occlusion, and 7 (20.6%) had worsening occlusion. Data for cases treated with new PGA-containing coils together with bare platinum coils were also analyzed separately. Intraprocedural adverse events were noted in 4 cases (7.8%), but there were no clinical sequelae. There were no rebleeds in the follow-up period.CONCLUSION: New PGA-containing coils show no excess in procedural and periprocedural complications over bare platinum coils, and the recanalization rate is comparable with bare platinum coils in the short term.